DIETARY HABITS OF NIGHT SHIFT WORKERS – A REASON OR AN EXCUSE FOR POOR NUTRITION - Anđelković, Svetlana; Babić, Maja (Srpski medicinski časopis Lekarske komore, 2024)
The availability of artificial light and light-emitting devices has changed human life in relation to time, enabling 24-hour health care, trade, and production, as well as the expansion of social life around the clock. In Europe, about 21% of the labor force consists of shift workers. 10% of the employed population work evening shifts or the night shift, and 7% of employees in Europe regularly work the night shift. According to the Bureau of Labor Statistics, more than 15 million Americans work the night shift. Shift work, especially night-time work, seriously affects dietary habits. It is known that night-time work produces a conflict between the socially determined rhythm of eating and the circadian biological rhythms related to the feeling of hunger, satiety, as well as the metabolism itself. Night meals cause disorders of intestinal motility, affect digestion, absorption, but also the utilization of nutrients and possible medical therapy (if the individual has one). From the point of view of chronobiology, humans belong to diurnal species, which to a certain extent explains why night shift workers have a decreased appetite at night, when the human body is programmed for rest and fasting, as well as for endogenous mobilization of glucose. From the psychosocial aspect, shift workers usually experience a discrepancy between their daily routines (including the meal schedule) and those they have with family and friends, which further leads to even more severe disorders of dietary habits. However, it is difficult to give dietary recommendations regarding nutrition. Firstly, there are no clear views on whether night shift workers should eat during the night hours or not. Secondly, even if night eating is encouraged, definitive evidence is lacking on which types of food should be consumed and which should be avoided. Thirdly, the most nutritious foods may not be available at that time of night. Finally, eating at night certainly has an impact on the metabolism. With all the above in mind, we have tried to provide some useful guidelines regarding these issues.